Suicidal thoughts and their relationship with risk factors which are associated with anxiety and depression among young people in the Palestinian society - Al-Hallaq, Iyad Salim; Jaradat, Nisreen Issa (Journal of Educational and Psychological Sciences, 2018)
This study aimed to detect the prevalence of suicidal thoughts and their relationship with risk factors which are associated with anxiety and depression among young people in the Palestinian society. And to achieve the objectives of the study , the researcher hired of a scale for measuring suicidal thoughts , anxiety and depression , which was applicated on a sample of 1210 people, by 55.8% male and 44.2% female, in the age group between (16 – 30) years.Data processing has used statistical average and standard deviations and the (t-test) , the test of variance and Pearson correlation coefficient , and the Crnobachs alpha reliability equation. The result of the study indicated that: 13.9% have suicidal thoughts, 10.6% had tried to commit suicide, 10.2% have a future plan to commit suicide, and 7.8% have told people to attempt suicide, 49% have anxiety, and 44.8% have depression, the results showed the presence of a positive correlation between positive thoughts of suicide, anxiety and depression.Also the results indicated that the suicidal thoughts and anxiety were more prevalent in Hebron, followed by Bethlehem, Ramallah and Jericho. But they indicated that the depression was more prevalent in Nablus, since 50-78% has a willingness to ask for help, conversely 52.2% do not show any willingness to ask for help.Based on, the previous findings, the study recommend the need to raise the awareness of the seriousness of the suicide ideas, and to intensify efforts in formal and informal institutions to provide and support and protect the youth people, and also to provide them of Mental health services, and outreach programs to educate them in how to front their problems and ways to solve them rationally.
Keywords: suicidal thoughts; suicide; risk factors; anxiety; depression; youth; Palestinian society